2012
DOI: 10.9790/3008-0240105
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Knowledge & Awareness of Medical Doctors Towards Radiation Exposure Risk At Tikur Anbessa Specialized Referral And Teaching Hospital, Addis Ababa, Ethiopia.

Abstract: Increasing concern has recently been expressed in the literature that the referring doctor's knowledge of radiation doses incurred during radiological procedures is inadequate. Such information may be particularly relevant when the expansion of imaging technology is considered. Hence the objective of this work is to assess the awareness of physicians about radiation dose and hazards of radiation. The study was performed among medical doctors at Tikur Anbessa Specialized Referral Teaching Hospital, the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…To find what is actually done, how much is gained by students and how much they apply is really a concern. Few studies conducted in various countries have used similar questionnaires to find out the knowledge and attitudes of medical personnel and have revealed disappointing results [10][11][12][13]. The studies call for urgent measures to impart education about radiation safety and implementation of adequate measures to decrease radiation exposure [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…To find what is actually done, how much is gained by students and how much they apply is really a concern. Few studies conducted in various countries have used similar questionnaires to find out the knowledge and attitudes of medical personnel and have revealed disappointing results [10][11][12][13]. The studies call for urgent measures to impart education about radiation safety and implementation of adequate measures to decrease radiation exposure [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Some studies have shown poor knowledge in radiation biology among the practitioners; both dental and medical. [17,18] as well as in radiographers [19] and other health workers. [20,21] Obtained results from this study also showed a similar result.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present work was to evaluate the knowledge and awareness of physicians about the hazards of radiological examinations on the health of workers and their patients in Saudi Arabia. Several studies estimate the knowledge and awareness of physicians about the hazards of radiological examinations in Asia, Africa and Europe (Abdellah, Attia, Fouad, & Abdel-Halim, 2015;Alhasan, 2016;Hamarsheh & Ahmead, 2012;Illian, 2011;Madrigano, Abrão, Puchnick, & Regacini, 2014;Sin et al, 2013;Sundaran, 2017;Zewdneh, Dellie, & Ayele, 2012). Some of these studies showed a lack of knowledge and awareness in radiation protection such as African physicians (Abdellah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%